Indicadores utilizados para avaliar desfechos econômicos em pacientes com doenças crônicas que contribuem para o risco cardiovascular atendidos por farmacêuticos em ambulatório - Carvalho, Gabriela Andrade Conrado (2022)
Introduction. In the last decades, health expenditures, mainly in the elderly population, have been a great concern for health systems around the world, which have a direct economic impact with population aging. Economic evaluations provide information to stakeholders and decision makers so that resources are used efficiently. Therefore, the presence of the pharmacist may avoid some unnecessary expenses, as well as improve health outcomes. So, this study carried out a scoping review in order to identify which indicators are used to assess economic and pharmacoeconomic outcomes in elderly patients with cardiovascular risk diseases and, based on these indicators, identify which services are considered more likely to reduce costs in health. Objective. Identify which indicators are used to assess economic and pharmacoeconomic outcomes in elderly patients with chronic diseases that contribute to cardiovascular risk treated by pharmacists in an outpatient setting. Method. This study was divided into two steps. In the first step, a scoping review was carried out to understand the financial burden on elderly patients with chronic diseases that contribute to cardiovascular risk treated by pharmacists on an outpatient basis. In the second step, another scoping review was performed with the objective of identifying the indicators used in pharmacoeconomic studies in elderly patients with chronic diseases that contribute to cardiovascular risk treated by pharmacists on an outpatient basis. In order to understand which economic indicators are more related to clinical and humanistic indicators. Results. In the first step, 13 articles were included. Most studies were specific to patients with diabetes. The most used indicators were The most used indicators were pharmacotherapeutic monitoring, identification and prevention of drug-related problems and health education. The average cost per patient and the cost of their medications were the most reported financial indicators. In the second step, twelve articles, published in English in four continents: America, Asia, Oceania, and Europe, were included. Most studies have been conducted in the United States. For the cost-effectiveness analysis, the following clinical indicators were used: glycated hemoglobin, cholesterol levels, and blood pressure. For the cost-utility analysis, the quality-adjusted life years (QALY) was considered, and for the cost-benefit analysis, the additional financial benefit for clinical improvement was calculated. The cost category addressed in most articles was direct medical cost, with labor cost and cost per intervention associated with reduction of clinical measures being the most reported among the studies. Conclusion. The cost indicators and outcome measures available in the literature were raised in this review and, in general, the clinical benefit of the service outweighed the cost of intervention, especially when associated with more complex pharmaceutical clinical services. In this way, it is hoped that the indicators gathered will help towards a more comprehensive assessment of the financial burden related to the disease and help guide future policies in this area.